Islamic Legal Analysis of the Dual Income No Kids (DINK) Phenomenon from the Perspective of Maqashid al-Shari’ah and the Theory of Maslahah - Hidayati, Noor Kholifah (Universitas Islam Indonesia, 2025)
This article examines the phenomenon of Dual Income No Kids (DINK) from the perspective of Islamic law using the maqashid al-shari’ah approach and the theory of maslahah. DINK is a lifestyle choice in which married couples consciously decide not to have children in pursuit of careers, financial stability, or personal freedom. This phenomenon raises normative issues in Islam because it is not in line with the objectives of marriage, namely, to preserve lineage (hifz al-nasl) and protect life (hifz al-nafs). This study aims to understand the Islamic legal perspective on the decision of married couples to live without children through the DINK concept. This is descriptive-qualitative research using a normative theological approach. The results show that the DINK decision can be justified according to shari’ah, provided it is based on considerations of public benefit (maslahah) and legitimate responsibility. However, if it is driven by hedonistic or individualistic motives without a valid shari’ah-based reason, then the decision has the potential to contradict the maqashid al-shari’ah. Therefore, the study suggests that a reflective, adaptive, moderate, and contextual approach in Islamic law is needed to respond to this social phenomenon, to ensure alignment with the objectives of marriage in shari’ah, as well as the goal of forming an excellent generation in Islam.